Speculations II - Austin, Michael; Ennis, Paul J.; Gokey, Thomas (punctum books, 2020)
From the Editorial Introduction: "If the first volume of Speculations was enough of an explicit wager, a willing blind leap in the terra incognita of the publishing world, then this volume forces us to stop and evaluate the reasons for the journal's protracted existence. This is all the more important when we consider how the range of meanings of the term 'speculative realism' seems to be growing-with increasing numbers of thinkers situating themselves in its trail, or holding a somewhat cautious interest in it-while its e ective reference seems nowhere to be found. ..."